The Great Transition in Indian Museums: From NMML to PMML - ADITI SINGH (The Journal of Indian and Asian Studies)
The transition of the Nehru Memorial Museum and Library (NMML) to Pradhanmantri Sanghrahalaya/Prime Ministers Museum and Library Society (PMML) in 2023 (while the Pradhanmantri Sangrahalaya was inaugurated on April 14, 2022, the NMML was officially renamed as the PMML with effect from August 14, 2023) signifies a marked change in the museum ecosystem of India. It reflects a shift in how India’s history and politics are presented to the citizenry. Several governments have undertaken similar renaming exercises globally in the past. The move of changing the status of NMML from that of a distinguished establishment highlighting the life and work of India’s first Prime Minister, Jawaharlal Nehru, to one of a museum dedicated to all former Prime Ministers of India has elicited both commendation and criticism. The proponents of the idea laud the all-inclusive representation of all Prime Ministers in India, saying that it gives a fuller account of Indian governance and political history over time, whereas those against it argue that this change could undermine the focus on Nehru’s legacy. This paper argues that this is a huge departure from how museums depict India’s political past. This shift is not simply bureaucratic; rather, it holds deep symbolic meaning about different notions of nationhood and its historical recollection in India. Thus, this research examines government institutions’ roles in museum gatekeeping and consequences of governmental decision-making about renaming particular establishments. This paper not only describes how certain instruments (here, museums) are mobilized to construct the “truth,” it also broaches the theme that even such instruments (technologies of truth-production) have their own histories (susceptible to change in form and content through time/contexts).